Analisis Penerapan PSAK No. 109 Tentang Pelaporan Keuangan Akuntansi Zakat, Infak/Sedekah Pada Baznas Kabupaten Majalengka - Mukhlis Harvian; Alifah Sukma Asih; Firman Yudhanegara; Iwan Setiawan (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This studyiaims toiexamine theirecognition and measurement process related to the receiptiand distribution ofifunds carried out by BAZNAS Majalengka Regency, analyze the implementation of its financial reports, and assess their compliance with PSAK 109. Using a qualitativeidescriptive method, data wasicollected throughiinterviews. The research findings indicate that the financial reporting of BAZNAS Majalengka Regency adheres to PSAK 109, covering the receipt and distributioniofizakat, infaq, and sadaqah funds. Every economic transaction is systematically recorded, and the financial reports comply with applicableiregulations, including the treatment of non-halal funds in accordance with sharia iprinciples. In terms of recognition and presentation, BAZNAS Majalengka Regency applies the double-entry recording system, which is considered effective and efficient. Overall, the financial reports prepared align with PSAK 109 in terms of recognition, measurement, and presentation.